Regional Governance on Covid-19 Vaccination in The Southeast Asia - Deasy Silvya Sari; Mas Halimah; Akim Akim; Ali Zahid (Universitas Padjadjaran, 2022)
One of the efforts to prevent the spread of Covid-19 is the Covid-19 vaccine. Everyone in the world has the right to access a Covid-19 vaccine, so governance is needed to guarantee that vaccine distribution is fair and equal. This article aims to discuss the regional governance of the COVID-19 vaccination program in Southeast Asia. Furthermore, the concept of regional governance and systematic literature study methods was used. The results showed that states in southeast asia have done bilateral cooperation with vaccine-producing eventough companies or states. On the scheme of regional governance, ASEAN becomes a fasilitator of vaccine distribution in order to guarantee that ASEAN members get the vaccine.